Odpowiedzi

2009-09-29T18:03:39+02:00
A) 4 i 3/6 + 2 i 2/6 * 9/2 = 6 i 5/6 * 9/2 = 41/6 * 9/2 = 123/4 = 30 i 3/4
b) 36/7 * 13/9 -6 : 14/3 = 52/7 - 18/14 = 104/14 - 18/14 = 86/14
c) 7/2 *(9/4 -3/2 : 6) = 7/2 * (9/4 - 36/4) = 7/2 * (-27/4) = - 189/8
d) 47/9 - 7/6= 470/90 - 105/90 = 365/90

---------------------
11/3 * (5/4-1/2) = 11/3 *(5/4-2/4) = 11/3* (3/4) = 33/12
2009-09-29T18:08:20+02:00
4 1/2 +2 1/3 razy 4 1/2 = 4 3/6 + 7/3 razy 9/2 = 4 3/6 + 63/6 = 4 3/6 + 10 3/6=
=14 6/6= 15

5 1/7 razy 1 4/9 -6:4 2/3= 36/7 razy 13/9 - 6: 14/3 = 52/7 -6 × 3/14=
= 52/7-9/7 = 43/7 = 6 1/7

3 1/2 razy (2 1/4 - 1 1/2:6)=3 1/2 razy (2 3/12 - 3/2 razy 1/6) =
= 3 1/2 razy ( 2 3/12 - 3/12) = 3 1/2 rzay 2 = 7

5 2/9 -1 1/6 = 5 4/18 - 1 3/18 = 4 1/18

3 2/3 razy (1 1/4 - 1/2 )= 3 2/3 razy ( 5/4 - 2/4) = 3 2/3 razy 3/4 =
= 11/3 razy 3/4 = 11/4